Colorimetric Determination of Tungsten and Molybdenum in Biological Samples - Aaron Donaghy; Gerrit Schut; Nana Shao; Farris Poole; Michael Adams (Bio-Protocol)
Molybdenum (Mo) and tungsten (W) are elements that are utilized in biological systems. They are typically incorporated into the catalytic sites of enzymes coordinated to an organic pyranopterin cofactor; Mo may also be present in the form of a FeMo cofactor. While Mo is used by all branches of life, only a few microbes are able to utilize W. In order to study Mo- and W-dependent enzymes, it is important to be able to measure Mo and W in biological samples. Methods for determining Mo and W content in biological samples currently involve expensive and time-consuming processes like inductively coupled plasma mass spectrometry (ICP-MS) and chelation ion chromatography. There are less intensive colorimetric methods for measuring W in abiotic samples, but these have not been adapted to biological samples like cytosolic extracts and purified proteins. Herein, we developed a colorimetric assay based on the complexation of quercetin to molybdate (MoO42-) or tungstate (WO42-), the oxyanion forms of Mo and W that readily form in denatured biological samples. In the assay, the absorbance of quercetin is redshifted proportionally to the concentration of tungsten or molybdenum, which can be measured spectrophotometrically. This protocol provides a rapid method for screening biological samples for both Mo and W, although it does not distinguish between them.